A Novel In Vitro Protocol for Inducing Direct Somatic Embryogenesis in Phalaenopsis aphrodite without Taking Explants - Jia-Hua Feng; Jen-Tsung Chen (The Scientific World Journal)
An alternative in vitro protocol for embryo induction directly from intact living seedlings of Phalaenopsis aphrodite subspecies formosana was established in this study. Without the supplementation of plant growth regulators (PGRs), no embryos were obtained from all the seedlings when cultured on the solid medium. In contrast, embryos formed from the seedlings on the 2-layer medium and the 2-step culture system without the use of PGRs. It was found that the age of the seedlings affected embryo induction. The 2-month-old seedlings typically had higher embryogenic responses when compared with the 4-month-old seedlings in the 2-layer medium or 2-step system. For the 2-month-old seedlings, 1 mg/L TDZ resulted in the highest number of embryos at the distal site of the shoot. However, on the leaves’ surface, 0.5 mg/L TDZ induced the highest number of embryos. When the 2-month-old seedlings were cultured using the 2-step method at 1 mg/L of TDZ, the highest embryogenic response was obtained, with an average of 44 embryos formed on each seedling. These adventitious embryos were able to convert into plantlets in a PGR-free 1/2 MS medium, and the plantlets had normal morphology and growth.